Synchronous GABA(A)-receptor-dependent potentials in limbic areas of the in-vitro isolated adult guinea pig brain - Uva, Laura (Eur J Neurosci, 2009)
Epileptiform discharges are known to reflect the hypersynchronous glutamatergic activation of cortical neurons. However, experimental evidence has revealed that epileptiform synchronization is also contributed to by population events mediated by GABA(A) receptors. Here, we analysed the spatial distribution of GABA(A)-receptor-dependent interictal events in the hippocampal/parahippocampal region of the adult guinea pig brain isolated in vitro. We found that arterial perfusion of this preparation with 4-aminopyridine caused the appearance of glutamatergic-independent interictal potentials that were reversibly abolished by GABA(A) receptor antagonism. Laminar profiles and current source density analysis performed in different limbic areas demonstrated that these GABA(A)-receptor-mediated events were independently generated in different areas of the hippocampal / parahippocampal formation (most often in the medial entorhinal cortex) and propagated between interconnected limbic structures of both hemispheres. Finally, intracellular recordings from principal neurons of the medial entorhinal cortex demonstrated that the GABAergic field potential correlated to inhibitory postsynaptic potentials (membrane potential reversal, −68.12 ± 8.01 mV, n = 5) that were interrupted by ectopic spiking. Our findings demonstrate that, in an acute seizure model developed in the adult guinea pig brain, hypersynchronous GABA(A)-receptor-mediated interictal events are generated from independent sources and propagate within limbic cortices in the absence of excitatory synaptic transmission. As spared or enhanced inhibition was reported in models of epilepsy, our data may support a role of GABA-mediated signaling in ictogenesis and epileptogenesis.